Design Framework for A School Playground - Syaiputra Wahyuda Meisa Diningrat (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
Playing in outdoor learning environment is pivotal to the life of children. Allowing them to interact with playground promise the children to enhance their well-being and healthy growth and development. Experts believe in capabilities of playground on supporting not only the childrens growth, but also the childrens development. In contrast, research showed lack of appropriateness playground with the childrens need become the hardest challenge for some educators. Therefore, this study aims to provide theoretical framework in design a school playground that fits with the childrens needs. The methodology used for this study has been done through analyze the recent literature such as books, journals and research related to design playground. The study has attempted to answer questions such as principles of playground design, causes of childrens use the playground and the design framework for playground that suitable for childrens needs. In summary, this article will facilitate educators to design higher quality playground that fit with the needs of the children. Thus, it is recommended for educators to use design framework for a school playground in order to minimize the failure in design and develop playground. Therefore, the effort to facilitate the childrens growth and development through a playground become effectively.